Earthquakes: notes about seismic activity in Montes Claros/MG - Oliveira, Rachel Inêz Castro de (2012)
Almost all the seismic activities in the world happen on tectonic plate boundaries. Inside the plates, the seismicity is relatively weak. Brazil is located inside South-American plate, it is far from the plate east and west boundaries. But it does not mean seismic activities do not happen in Brazil. Actually, almost all the seismic activities in Brazil are considered low magnitude ones. There are only two earthquakes larger than 6 on Richter scale were reported: one of them happened in Serra do Tombador in Mato Grosso in 1955. It was a 6.2 earthquake. The other one was a 6.3 earthquake and it happened in Espírito Santo seaside in 1955. In December, 2007, it was reported a 4.6 seismic activity in Minas Gerais North area, in Itamarandiba. Because of it, Brazil registered the first fatal victim of an earthquake. This study aims to take into account basic seismicity, seismic activities in Brazil, and seismic activities in Montes Claros/MG. Methodologically, it brings a bibliographic review of thesis, dissertations, books, and papers about the subject. It is worth mentioning that despite the seismic activities inside the plate are not considered as important ones as the one on the boundaries of a plate, they may be studied and monitored, and then it will be possible to evaluate the seismic risks in the area where they happen.